Congenital Diaphragmatic Hernia, Predictors of Survival and Adverse Outcomes - Kamal Ali MD; Nemer Aljuaid MD; Saleh S. Algarni PhD; Abadi Ghazwani BS; Saad Alshreedah BS; Nawaf Alghamdi MD; Mohamad Alreefi MD; Abdurhman Alsaif MD; Naif Alotaibi BS; Wejdan Alzahrani MD; Saif Alsaif MD (SAGE Publishing, 2024)
Objective. To examine the postnatal predictors of survival and adverse outcome among Congenital Diaphragmatic Hernia (CDH) infants. Method. Six-year retrospective review of CDH infants born at tertiary neonatal unit. Results. Forty infants with CDH were included; 27 (67.5%) survived to discharge. Non-survivors had a higher best, mean, and highest oxygenation index (OI) ( P  < .001) on day 1 compared to survivors. Best (AUC = 0.917), mean (AUC = 0.945), and highest (AUC = 0.923) OI on day 1 were all predictive of mortality. The mean day-1 OI had a significant correlation with the duration of ventilation (DOV) (Spearman rho correlation coefficient ( r S ) = .549, P  = .004), TTS ( r S  = .526, P  = .007), and the length of hospital stay (LOS) ( r S  = .497, P  = .012). The best and highest day-1 OI also correlated significantly with DOV, TTS, and LOS. Conclusion. First day OIs were excellent predictors of survival and have a significant correlation with the DOV, LOS, and TTS in infants with CDH.